Adherence to antiretroviral therapy among HIV patients visiting HIV counselling centres in selected hospitals, Benin City, Edo State - EHWARIEME, Timothy .A; UNIGWE, Joy K; IDHIGU, Kingsley U (International Journal of Nursing, Midwife and Health Related Cases, 2020)
The introduction of antiretroviral drugs over the past two decades has helped greatly towards controlling HIV/AIDS infection outcome. However its effectiveness depends largely on adherence to the drug. This study was undertaken to assess adherence to antiretroviral drugs among HIV patients visiting HIV counselling centres in selected hospitals, Benin City, Edo state. The study was carried among 220 HIV patients visiting three selected counselling centre in Benin City using convenient sampling technique and a self-structured questionnaire. Data collected were analysed using descriptive statistics and inferential statistics such as Chi square, multivariate logistic regression and ANOVA were used to test hypothesis at 5% level of significance. Result shows 78(35.9%) have poor knowledge, 60(27.6%)) have moderate, while the remaining 79(36.40) have good knowledge. majority 171(77.7%) have good adherence level. factors are food (2.66±1.03), Unavailability drugs (2.76±0.98), drug toxic effect (2.61±0.88), Stigmatization (2.60±0.96) were found to affect adherence. There was no significant relationship (p>0.05) between adherence of sociodemographic characteristics. However significant difference (p<0.05) was found in the level of knowledge among HIV patient. Multivariate logistic regression showed that respondents that are 18 – 20 years are ten times (O.R = 10.39; C.I = 1.01-107.10) more likely not to adhere than those above 50years. Also respondents with tertiary education are 19% (O.R. 0.81; C.I. = 0.15 – 4.20) less likely not to adhere than those with no education and Christians are 50% (O.R. = 0.50; C.I. = 0.12-2.05) less likely not to adhere than those with traditions/other religion. Conclusion more awareness campaigns and other interventions are needed to improve and sustain the present level of adherence.
Keywords: ACE: Reproductive Health Innovation; CERHI; University of Benin; Nigeria; adherence; antiretroviral drug; HIV patients; counselling centres